A Heterogeneous Energy Wireless Sensor Network Clustering Protocol. (26th May 2019) - Zeng, Mengjia; Huang, Xu; Zheng, Bo; Fan, Xiangxiang
Abstract : The Low-Efficiency Adaptive Clustering Hierarchical (LEACH) protocol, a hierarchical routing protocol, has the advantage of simple implementation and can effectively balance network loads. However, to date there has been a lack of consideration for its use in heterogeneous energy network environments. To solve this problem, the Energy-Coverage Ratio Clustering Protocol (E-CRCP) is proposed, which is based on reducing the energy consumption of the system and utilizing the regional coverage ratio. First, the energy model is designed. The optimal number of clusters is determined based on the principle of "minimum energy consumption", and the cluster head selection is based on the principle of "regional coverage maximization". In order to balance the network load as much as possible, in the next iteration of cluster head selection, the cluster head with the lowest residual energy and the highest energy consumption is replaced to prolong the network's life. Our simulated results demonstrate that the proposed method has some advantages in terms of longer network life, load balancing, and overall energy consumption in the environment of a heterogeneous energy wireless sensor network.